The Register of Rice Cultivation in Kesugihan District, Cilacap Regency, and Its Relevance to Javanese Language Learning at the Junior High School Level - Haryanti; Endang Nurhayati (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2026)
This study examines the decline in intergenerational transmission of traditional agricultural vocabulary within Javanese-speaking farming communities, particularly in rice cultivation. The study aims analyze the rice cultivation register in Kesugihan District, Cilacap Regency, and to examine its relevance to Javanese language learning at the junior high school. Data were collected through field observation, semi-structured interviews, surveys, and documentation involving farmers, village officials, agricultural extension officers, and members of farmer groups. The data were analyzed using register theory and functional linguistic perspectives through stages of transcription, categorization, contextual interpretation, and functional analysis. The findings reveal the rice cultivation register in Kesugihan District reflects a systematic linguistic variation organized into three stages: pre-planting, land preparation, and planting. The registers are characterized by distinctive ngapak Javanese lexical forms such as rumbras, kluyon, nggebal, ngepyak, demplot, ombol, and nyidhangi, which function as technical communication tools, markers of work procedures, and carriers local knowledge. Linguistically, the study demonstrates relationship between register formation, social activity, and cultural practices within agrarian communities. The findings also affirm agricultural registers can serve contextual and culture-based teaching materials in Javanese language education by enriching students vocabulary mastery, introducing dialectal variation, and strengthening local wisdom-oriented learning at the junior high school.